Efforts of Leaders in Regional Apparatus Organizations (OPD) to Cultivate Innovation in Public Services - Fathur Rahman; Wawan Sobari; Ibnu Asqori Pohan (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
In recent years, innovation has become an instrument to improve the quality of services to the public. From year to year, the number of participants from innovation competitions was increased. However, after the competition over, innovation does not developed and tends to wither or even die. Therefore, there must be an effort made by leaders in every Regional Apparatus Organization (OPD). This study aimed to explain the efforts made by leaders in local governance organizations to cultivate innovation in public service. The data in this paper were collected through observations to each service unit, interviews with leaders, technical managers of innovation units in each OPD and a study of documentation of regional innovation data base reports. The findings, leaders must have a commitment to the institutions and employees to innovate; leaders who are adaptive and dare to take risks; accepts user’s complaints so they changed; collaborate and integrate with stakeholders to designed the public service innovation. Innovation is the result of collective work; leaders and employees have an influence on the sustainability of public service innovation.Keyword: Leaders, Regional Apparatus Organizations, Innovate, Public Service